Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1530/eor-21-0108
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosed and maltreated scaphoid fractures – costly both for society and patients: A review of filed claims to the Swedish National Patient Insurance Company 2011–2018

Abstract: Misdiagnosed and maltreated scaphoid fractures filed to the Swedish National Patient Insurance Company (LÖF) 2011–2018 were analyzed in terms of complications and costs for society. All filed claims are database-registered (altogether 200 000 claims since 2000). This database was assessed in June 2019 through injury ICD10-SWE-diagnoses. Demographics, complications, complaints, corrective surgeries and costs were analyzed. The numbers of claims for scaphoid fractures were reviewed and compared with all claims. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…These are only the costs of hardware removal and sick leave; they do not include the time saved in the operation theater at the initial operation and other costs, such as those of additional visits and medication. In a very recent publication, Andersson et al [15] described that the frequency of settled claims of scaphoid fractures was 20% higher than for general complaints [15]. Furthermore, they found that 56% of the claims were due to delayed diagnosis and 41% were due to misdiagnosis [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are only the costs of hardware removal and sick leave; they do not include the time saved in the operation theater at the initial operation and other costs, such as those of additional visits and medication. In a very recent publication, Andersson et al [15] described that the frequency of settled claims of scaphoid fractures was 20% higher than for general complaints [15]. Furthermore, they found that 56% of the claims were due to delayed diagnosis and 41% were due to misdiagnosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…C The skin incision was pulled proximally with a narrow-wound hook and, at the same time, the wrist was bent so that the protruding material of the cortical bone screw could be sawn off just above the bone surface in a subsequent step Sailer et al Journal of Orthopaedics and Traumatology (2023) 24:6 chevron osteotomy, and by Hanslik-Schnabel et al [12] when using it for the correction of hallux rigidus with and without deformities. Scaphoid fractures account for 50-90% of all carpal fractures in young active patients [13][14][15]. Approximately 10% [13,[16][17][18] of all scaphoid fractures progress to nonunion, dependent on the fracture location, fracture displacement, instability and time to treatment [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study from Lund (Sweden) , all claims relating to scaphoid fractures over a seven-year period from 2011 to 2018 were analyzed to look for complications and the associated costs to society. 6 A total of 128 claims were identified, 78 (61%) of which were judged as avoidable by the claim registry and the expert physician. Overall, 72 of these were filed because of delayed diagnosis and consequently delayed treatment.…”
Section: Misdiagnosed and Maltreated Scaphoid Fractures - Costly Both...mentioning
confidence: 99%
“…In Sweden, all claims filed to the Swedish National Patient Insurance Company (LÖF) are registered in a database. In this study from Lund (Sweden), all claims relating to scaphoid fractures over a seven-year period from 2011 to 2018 were analyzed to look for complications and the associated costs to society 6. A total of 128 claims were identified, 78 (61%) of which were judged as avoidable by the claim registry and the expert physician.…”
mentioning
confidence: 99%